2015
DOI: 10.1186/s40733-015-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Small airway dysfunction and bronchial asthma control : the state of the art

Abstract: According to national and international guidelines, achieving and maintaining asthma control is a major goal of disease management. In closely controlled clinical trials, good asthma control can be achieved , with the medical treatments currently available, in the majority of patients , but large population-based studies suggest that a significant proportion of patients in real-life setting experience suboptimal levels of asthma control and report lifestyle limitations with a considerable burden on quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 144 publications
1
15
0
2
Order By: Relevance
“…Studies worldwide showed that the prevalence of asthma control was not optimal in large per cent of asthmatic patients, per cent of poor controlled asthma were ranging from 44% to 57%, and there were a high percent of rescue medication usage . In Jordan, one study showed that 71% of asthmatic patients poorly controlled .…”
Section: Discussionmentioning
confidence: 99%
“…Studies worldwide showed that the prevalence of asthma control was not optimal in large per cent of asthmatic patients, per cent of poor controlled asthma were ranging from 44% to 57%, and there were a high percent of rescue medication usage . In Jordan, one study showed that 71% of asthmatic patients poorly controlled .…”
Section: Discussionmentioning
confidence: 99%
“…Результаты представленных исследований позволяют сделать вывод о том, что ОМ разрывает «порочный круг» индукции и поддержания IgE-зависимого воспаления, существенно влияет на ремоделирование, в том числе и мелких ДП [4,8,[12][13][14]. Таким образом, на сегодняшний день имеются основания рассматривать ОМ в качестве лекарственного средства, модифицирующего болезнь.…”
Section: влияние омализумаба на ремоделирование дыхательных путейunclassified
“…В настоящее время имеются многочисленные доказа-тельства того, что частые дневные симптомы БА, повторяю-щиеся ночные эпизоды, плохой контроль, высокая БГР, увеличение числа обострений и потребности в системных кортикостероидах (СКС), развитие стероидозависимой БА ассоциированы с вовлечением мелких ДП [8]. Результаты трансбронхиальной биопсии демонстрируют, что мелкие ДП являются основным местом воспаления при тяжелой БА: инфильтрат состоит из эозинофилов, Т-лимфоцитов, нейтрофилов и макрофагов.…”
unclassified
“…Human small airways consist of membranous, terminal, and respiratory bronchi of less than 2 mm diameter (Cottini et al 2015). In mice, small airways are defined as those having a diameter between 0 and 400 lm (Liu et al 2006;Sera et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, small airways are defined as those having a diameter between 0 and 400 lm (Liu et al 2006;Sera et al 2007). Several studies conducted over three decades ago demonstrated that the small airways are pathways of low resistance, contributing to less than 10% of the total resistance to airflow (Cottini et al 2015). For this reason, the small airways were originally described as the "quiet zone" of the lungs (Harrison et al 2008;Carr et al 2017).…”
Section: Introductionmentioning
confidence: 99%